Development of artificial diets for rearing of adult lady bird beetle Coccinella septumpunctata in laboratory - SINGH, S P; SINGH, Y P; KUMAR, SANDEEP; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2014)
Adult lady bird beetle, Coccinella septumpunctata was reared on semi-solid and liquid artificial diets in the laboratory at 25±1°C temperature and 70±5% relative humidity during 2011-12 and 2012-13. In first effort ten combinations of artificial diet in semi-solid form comprising 3 basic ingredients, i.e. protinex, home food plus and nutripet in different combinations along with other ingredients like agar powder, yeast powder, honey, vitamin B-complex and vitamin E were evaluated against adult of C. septumpunctata. Methyl paraben and formaldehyde were used as diet preservatives. The adult of C. septumpunctata survived maximum period of 41.3 days on home food plus (100%) based diet while minimum period (15.7 days) on nutripet (100%) based diet. The survival pattern in other diets was recorded from 24.0 days to 39.7 days. Further efforts were made to improve the quality of diets and again 10 combination of artificial diets in liquid form based on five basic ingredients i.e. protinex, cerelac (baby feed), honey, home food plus and sucrose alone and with other food supplements like vitamin B-complex, vitamin E, ascorbic acid and yeast powder were prepared using methyl paraben and formaldehyde as diet preservatives. The diets devoid of other food supplements proved very excellent by adult longevity and per cent adult survival at different time interval. Longest adult survival (302 days) was recorded in cerelac based diet. However adult longevity on protinex, honey, home food plus and sucrose based diets was recorded as 296, 207, 258 and 296 days respectively.